Sabaudian Studies : Political Culture, Dynasty, and Territory (1400-1700) - Vester, Matthew A. (Matthew Allen) (Early modern studies series, 2013)
"This collection of interdisciplinary essays introduces the history and culture of the lands ruled by the sovereign house of Savoy during the late medieval and early modern periods, territories now part of France, Italy, and Switzerland. Because the Sabaudian realms were geographically, linguistically, and culturally diverse and did not evolve into a single modern nation-state, their early history has been overlooked by historians whose perspectives were often informed by a narrow, national framework. An international team of scholars offers new research that de-provincializes many of the existing rich scholarly assessments of the historical significance of these lands, which were important for rulers and subjects throughout early modern Europe. The volume explores the concept of Sabaudian studies and identifies historiographic developments and current trends in the field. Beginning with the geography and the history of the area, the essays examine Sabaudian political culture (diplomatic practice, judicial institutions, and political thought), dynastic representation (court festivals and celebrations, and the projection of dynastic prestige abroad, with attention to the sacred heritage of the house), and territorial domination (its fiscal, religious, feudal, and composite dimensions)."--Publisher's description